Bleaching Earths as Powerful Additives for Ru‐Catalyzed Self‐Metathesis of Non‐Refined Methyl Oleate at Pilot Scale. Issue 52 (16th August 2017) - Allard, Jessica; Curbet, Idriss; Chollet, Guillaume; Tripoteau, Fabien; Sambou, Sophie; Caijo, Frédéric; Raoul, Yann; Crévisy, Christophe; Baslé, Olivier; Mauduit, Marc
Abstract: A practical and cost‐effective ruthenium‐catalyzed self‐metathesis of non‐refined methyl oleate (85 %) derived from very high oleic sunflower oils was demonstrated at pilot scale using a robust and kg‐scale commercially available SIPr‐M71 pre‐catalyst. The simple addition of 1 wt % bleaching earths (Tonsil 110FF) to a thermally pretreated oil could efficiently prevent catalyst deactivation. Remarkably, without the need for filtration, the catalytic system was able to achieve a turnover number (TON) of more than 744 000 at a catalyst loading of only 1 ppm. At large scale (up to 200 kg), the equilibrium of the self‐metathesis reaction was reached within 1 hour at 50 °C under neat conditions at a very low 5 ppm catalyst loading to produce the expected primary metathesis products (PMP), that is, 9‐octadecene and dimethyl‐9‐octadecenoate, with a productive TON of 94900. Abstract : An efficient and cost‐effective pretreatment was proposed to mediate the Ru‐catalyzed self‐metathesis of non‐refined methyl oleate (( Z )‐1 ; 85 %) derived from very high oleic sunflower oils. The use of bleaching earths (Tonsil 110FF, 1 wt %) combined with a thermic pretreatment enabled metathesis under neat conditions with a catalytic loading as low as 0.0001 mol % (1 ppm) and impressive turnover number (TON) of 744 000. The robust catalytic process has proven to be efficient at pilot scale (200 kg) with a remarkable productive TON (94 900) for expected primary metathesis products 9‐octadecene (2 ) and dimethyl‐9‐octadecenoate (3 ).